A high-transmittance heat-insulating nano coating and preparation method thereof

By evenly dispersing a specific proportion of nanocesium tungsten bronze powder and other heat-insulating nanopowders in a specific proportion, the problem of poor light transmittance and heat-insulating effect caused by uneven dispersion of nanopowders is solved, and the effect of high light transmittance and high heat-insulating coatings is achieved, reducing building energy consumption.

CN119752302APending Publication Date: 2025-04-04SICHUAN YUGUANG OPTICAL GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510066933.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Nanocesium tungsten bronze is unevenly dispersed in the coating and easily agglomerated, resulting in low light transmission and poor thermal insulation effect.

Method used

A specific ratio of 30nm cesium tungsten bronze powder, 50nm ATO powder and 20nm lanthanum hexaboride powder are used as heat-insulating nanopowders, and combined with white oil, coupling agent, chain extender, resin particles, organic solvents and other components, the nanopowder is ensured to be evenly dispersed in the coating through high-mixing machine, planetary twin screw machine extrusion and high-speed stirring.

Benefits of technology

It achieves high visible light transmittance, high infrared and ultraviolet barrier rates, improves thermal insulation performance and reduces building energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244541430000071
    Figure BDA0005244541430000071
Patent Text Reader

Abstract

The invention discloses a high-transmittance heat-insulating nano coating and a preparation method thereof, and relates to the technical field of coatings. The invention discloses a high-transmittance heat-insulating nano coating and a preparation method thereof. The invention comprises the following steps: uniformly mixing modified heat-insulating nano powder, resin particles and additives in a high-speed mixer, and then co-extruding and cooling the mixture in a planetary twin-screw machine, and pelletizing the mixture; adding the pelletized composite particles into a solvent to dissolve the composite particles into a resin, adding a leveling agent, a dispersant, a coupling agent and a film-forming aid into the resin, and uniformly stirring the mixture in a high-speed mixer to obtain the high-transmittance heat-insulating nano coating. The high-transmittance heat-insulating nano coating prepared by the invention has high visible light transmittance, high infrared ray blocking rate, high ultraviolet ray blocking rate, good heat-insulating performance, and thus reduces building energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a high-transmittance heat-insulating nano coating and a preparation method thereof. Background Art

[0002] At present, the global greenhouse effect is intensifying, and energy conservation and emission reduction are common problems faced by the world's construction industry. The continuous increase in new buildings in my country each year has caused the proportion of building energy consumption in total energy consumption to continue to rise. Faced with this severe challenge, vigorously developing energy-saving buildings has become a consensus among all sectors of society.

[0003] Glass doors, windows and curtain walls are widely used in buildings. Since ordinary glass has almost the same transmittance to light of different wavelengths, it cannot effectively distinguish and block infrared and ultraviolet rays that carry a lot of heat. In addition, due to its high thermal conductivity, solar radiation energy can be conducted into the room, causing the indoor temperature to rise, thereby increasing the energy consumption of the building. It can be seen that improving the thermal insulation effect of glass is an important part of building energy conservation and emission reduction.

[0004] For glass, the main ways to achieve thermal insulation without significantly reducing light transmittance are LOW-E coating and metal oxide coating, which mainly improve its reflectivity and reduce surface temperature. However, its production difficulty and cost are high, and it is easily oxidized, resulting in reduced thermal insulation performance and service life. Transparent glass thermal insulation coating is a light-selective material, in which nano-cesium tungsten bronze can transmit visible light while shielding most of the near-infrared rays, so it is widely used in transparent insulating glass.

[0005] Nano-cesium tungsten bronze thermal insulation transparent coating is widely used in the field of glass thermal insulation and energy saving due to its high light transmittance and high thermal insulation. Nano-cesium tungsten bronze has high surface activity and adsorption due to its unique structure. In the process of dispersing nano-cesium tungsten bronze powder into slurry, there are problems such as uneven dispersion and easy agglomeration, which leads to reduced thermal insulation performance. Summary of the invention

[0006] The invention mainly solves the problem that cesium tungsten bronze is unevenly dispersed and easily agglomerated, resulting in low light transmittance and poor heat insulation effect.

[0007] In view of the above technical problems, the present invention proposes the following technical solutions:

[0008] A high-transmittance heat-insulating nano coating, the raw materials of which include the following components: white oil, coupling agent, chain extender, resin particles, organic solvent, resin, wetting and leveling agent, dispersant, ultraviolet additive, and film-forming additive.

[0009] Furthermore, the modified thermal insulation nano powder is composed of 30nm cesium tungsten bronze powder, 50nm ATO powder, and 20nm lanthanum hexaboride powder in a ratio of 7:2:1.

[0010] Furthermore, the white oil is at least one of 5# white oil, 7# white oil, 10# white oil, 22# white oil, and 32# white oil.

[0011] Furthermore, the coupling agent is at least one of vinyltrimethoxysilane A171, γ-aminopropyltriethoxysilane KH550, γ-(β-aminoethyl)aminopropyltrimethoxysilane KH791, γ-(2,3-epoxypropoxy)propyltrimethoxysilane KH560, γ-methacryloxypropyltrimethoxysilane KH570, vinyltrichlorosilane A150, titanate coupling agent TMC-102 and titanate coupling agent TMC-201.

[0012] Furthermore, the chain extender is at least one of 1,4-butanediol, trimethylolpropane, diethylaminoethanol, N-isopropylethylenediamine, triethylenetetramine, and ethylenediamine, and the resin particles are at least one of polyvinylidene fluoride particles, polyacrylic resin particles, and polyurethane particles.

[0013] Furthermore, the organic solvent is at least one of ethanol, isopropanol, ethyl acetate, butyl acetate, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, ethylene glycol diethyl ether, diethylene glycol butyl ether, and N-methylpyrrolidone.

[0014] Furthermore, the resin is at least one of fluorocarbon resin, polyurethane resin, acrylic resin and silicone resin.

[0015] Furthermore, the wetting and leveling agent is at least one of BYK346, BYK333, BYK-3550, TEGO Glide410, SURFYNOL420, DC-57, and Efka FL 3772.

[0016] Furthermore, the dispersant is at least one of BYK2015, BYK2018, BYK190, BYK110, BYK348, and TEGO-760W.

[0017] Furthermore, the UV additive is at least one of TINUVIN 400, TINUVIN 477, TINUVIN 479, TINUVIN 1130, TINUVIN 292, TINUVIN 1130, TINUVIN 123, and TINUVIN 249.

[0018] Furthermore, the film-forming aid is at least one of D-110, HT-100, N3390, D-120N, and D-3725.

[0019] The present invention also proposes a method for preparing a high-transmittance heat-insulating nano coating, comprising the following steps:

[0020] S1, add 0.01-0.5 parts of white oil, 0.1-1 parts of coupling agent, 0.01-1 parts of chain extender, and 30-60 parts of resin particles into a high-speed mixer and mix them at 1500 rpm to obtain A;

[0021] S2, 30nm cesium tungsten bronze powder, 50nm ATO powder, and 20nm lanthanum hexaboride powder are mixed in a ratio of 7:2:1 to obtain thermal insulation nanopowder, and then 10-30 parts of the thermal insulation nanopowder are added to A, and mixed to obtain B;

[0022] S3, blending and extruding B through a planetary twin-screw extruder, and pelletizing after cooling to obtain a composite modified thermal insulation nanomaterial C;

[0023] S4. Add 10-30 parts of C to 50-70 parts of organic solvent, stir until dissolved, and add 10-20 parts of resin, 0.1-1 parts of wetting and leveling agent, 0.1-1 parts of dispersant, 0.5-3 parts of UV additives, 0-5 parts of film-forming additives, stir evenly with a high-speed stirrer to obtain a high-transmittance heat-insulating nano coating.

[0024] The beneficial effects of the present invention compared with the prior art are: the heat-insulating nano-coating prepared by the present invention has high visible light transmittance, high infrared blocking rate, high ultraviolet blocking rate, good heat-insulating performance, and thus reduces building energy consumption by uniformly dispersing heat-insulating nano-powders such as cesium tungsten bronze in the coating. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. At the same time, the parts defined for materials appearing below are all parts by weight, which are used to express the mass ratio relationship between multiple components and are not dependent on specific weight units.

[0026] A high-transmittance heat-insulating nano coating, the raw materials of which include the following components by weight: white oil, coupling agent, chain extender, resin particles, organic solvent, resin, wetting and leveling agent, dispersant, ultraviolet additive, and film-forming additive.

[0027] The heat-insulating nano powder is composed of 30nm cesium tungsten bronze powder, 50nm ATO powder and 20nm lanthanum hexaboride powder in a ratio of 7:2:1.

[0028] The white oil is at least one of 5# white oil, 7# white oil, 10# white oil, 22# white oil and 32# white oil.

[0029] The coupling agent is at least one of vinyl trimethoxysilane A171, γ-aminopropyl triethoxysilane KH550, γ-(β-aminoethyl)aminopropyl trimethoxysilane KH791, γ-(2,3-epoxypropoxy)propyl trimethoxysilane KH560, γ-methacryloxypropyl trimethoxysilane KH570, vinyl trichlorosilane A150, titanate coupling agent TMC-102 and titanate coupling agent TMC-201.

[0030] The chain extender is at least one of 1,4-butanediol, trimethylolpropane, diethylaminoethanol, N-isopropylethylenediamine, triethylenetetramine, and ethylenediamine; the resin particles are at least one of polyvinylidene fluoride particles, polyacrylic resin particles, and polyurethane particles.

[0031] The organic solvent is at least one of ethanol, isopropanol, ethyl acetate, butyl acetate, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, ethylene glycol diethyl ether, diethylene glycol butyl ether, and N-methylpyrrolidone.

[0032] The resin is at least one of fluorocarbon resin, polyurethane resin, acrylic resin and silicone resin.

[0033] The wetting and leveling agent is at least one of BYK346, BYK333, BYK-3550, TEGO Glide410, SURFYNOL420, DC-57, and Efka FL 3772.

[0034] The dispersant is at least one of BYK2015, BYK2018, BYK190, BYK110, BYK348, and TEGO-760W.

[0035] The ultraviolet auxiliary agent is at least one of TINUVIN 400, TINUVIN 477, TINUVIN 479, TINUVIN 1130, TINUVIN 292, TINUVIN 1130, TINUVIN 123, and TINUVIN 249, and the film-forming auxiliary agent is at least one of D-110, HT-100, N3390, D-120N, and D-3725.

[0036] The present invention also proposes a method for preparing a high-transmittance heat-insulating nano coating, comprising the following steps:

[0037] S1, add 0.01-0.5 parts of white oil, 0.1-1 parts of coupling agent, 0.01-1 parts of chain extender, and 30-60 parts of resin particles into a high-speed mixer and mix them at 1500 rpm to obtain A;

[0038] S2, 30nm cesium tungsten bronze powder, 50nm ATO powder, and 20nm lanthanum hexaboride powder are mixed in a ratio of 7:2:1 to obtain thermal insulation nanopowder, and then 10-30 parts of the thermal insulation nanopowder are added to A, and mixed to obtain B;

[0039] S3, blending and extruding B through a planetary twin-screw extruder, and pelletizing after cooling to obtain a composite modified thermal insulation nanomaterial C;

[0040] S4. Add 10-30 parts of C to 50-70 parts of organic solvent, stir until dissolved, and add 10-20 parts of resin, 0.1-1 parts of wetting and leveling agent, 0.1-1 parts of dispersant, 0.5-3 parts of UV additives, 0-5 parts of film-forming additives, stir evenly with a high-speed stirrer to obtain a high-transmittance heat-insulating nano coating.

[0041] Embodiment 1:

[0042] 0.2 parts of 32# white oil, 0.1 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane KH560, 0.1 parts of chain extender trimethylolpropane, and 50 parts of polyurethane particles were added into a high-speed mixer and mixed at 1500 rpm to obtain A.

[0043] 30nm cesium tungsten bronze powder, 50nm ATO powder and 20nm lanthanum hexaboride powder were mixed evenly in a ratio of 7:2:1 to prepare thermal insulation nanopowder. Then, 10 parts of thermal insulation nanopowder were added to A and mixed evenly to obtain B. Finally, B was blended and extruded through a planetary twin-screw extruder, cooled and pelletized to obtain a composite modified thermal insulation material C.

[0044] Then add 30 parts of C into the organic solvent ethyl acetate and stir until dissolved, and add 10 parts of fluorocarbon resin ZHM-2, 0.5 parts of wetting and leveling agent BYK333, 0.5 parts of dispersant BYK348, 1 part of UV additive TINUVIN 123, 1 part of UV additive TINUVIN 400, and 2 parts of PDI film-forming additive D-3725N, and stir evenly with a high-speed stirrer to obtain a high-transmittance heat-insulating nano coating.

[0045] Example 2:

[0046] 0.2 parts of 32# white oil, 0.1 parts of titanate coupling agent TMC-201, 0.1 parts of chain extender 1,4-butanediol, and 50 parts of polyurethane particles were added into a high-speed mixer and mixed at 1500 rpm to obtain A.

[0047] 30nm cesium tungsten bronze powder, 50nm ATO powder and 20nm lanthanum hexaboride powder were mixed evenly in a ratio of 7:2:1 to prepare thermal insulation nanopowder. Then, 10 parts of thermal insulation nanopowder were added to A and mixed evenly to obtain B. Finally, B was blended and extruded through a planetary twin-screw extruder, and the composite modified thermal insulation material C was obtained by cooling and pelletizing.

[0048] Then, 30 parts of C were added to the organic solvent ethyl acetate and stirred until dissolved, and 10 parts of acrylic resin ZHM-2, 0.5 parts of wetting and leveling agent Efka FL 3772, 0.5 parts of dispersant BYK190, 1 part of UV additive TINUVIN 123, 1 part of UV additive TINUVIN 400, and 2 parts of PDI film-forming additive D-3725N were added, and stirred evenly with a high-speed stirrer to obtain a high-transmittance heat-insulating nano coating.

[0049] Example 3:

[0050] 0.2 parts of 32# white oil, 0.1 parts of titanate coupling agent TMC-102, 0.1 parts of diethylaminoethanol, and 50 parts of acrylic resin particles were added into a high-speed mixer and mixed at 1500 rpm to obtain A;

[0051] 30nm cesium tungsten bronze powder, 50nm ATO powder and 20nm lanthanum hexaboride powder were mixed evenly in a ratio of 7:2:1 to prepare thermal insulation nanopowder. Then, 10 parts of thermal insulation nanopowder were added to A and mixed evenly to obtain B. Finally, B was blended and extruded through a planetary twin-screw extruder, cooled and pelletized to obtain a composite modified thermal insulation material C.

[0052] 30 parts of C were added to the organic solvent ethyl acetate, stirred until dissolved, and 10 parts of acrylic resin ZHM-2, 0.5 parts of wetting and leveling agent BYK-3550, 0.5 parts of dispersant BYK110, 1 part of UV additive TINUVIN 123, 1 part of UV additive TINUVIN 400, and 2 parts of PDI film-forming additive D-3725N were added, and stirred evenly with a high-speed stirrer to obtain a thermal insulation nano coating.

[0053] The test results of the corresponding performance of the products formed in Example 1, Example 2 and Example 3 are shown in the following table It can be seen that the thermal insulation nano coating obtained by this method, the thermal insulation nano powder such as cesium tungsten bronze is evenly dispersed in the coating, has high visible light transmittance, high infrared blocking rate, high ultraviolet blocking rate, good thermal insulation performance, and reduces air conditioning energy consumption.

Claims

1. A high-transmittance heat-insulating nano coating, characterized in that: Its raw materials include the following components: white oil, coupling agent, chain extender, resin particles, organic solvent, resin, wetting and leveling agent, dispersant, ultraviolet additive, film-forming additive, and thermal insulation nano powder; The heat-insulating nano powder is composed of 30nm cesium tungsten bronze powder, 50nm ATO powder and 20nm lanthanum hexaboride powder in a ratio of 7:2:

1.

2. According to claim 1, a high-transmittance heat-insulating nano coating is characterized by: The white oil is at least one of 5# white oil, 7# white oil, 10# white oil, 22# white oil and 32# white oil; The coupling agent is at least one of vinyl trimethoxysilane A171, γ-aminopropyl triethoxysilane KH550, γ-(β-aminoethyl)aminopropyl trimethoxysilane KH791, γ-(2,3-epoxypropoxy)propyl trimethoxysilane KH560, γ-methacryloxypropyl trimethoxysilane KH570, vinyl trichlorosilane A150, titanate coupling agent TMC-102 and titanate coupling agent TMC-201; The chain extender is at least one of 1,4-butanediol, trimethylolpropane, diethylaminoethanol, N-isopropylethylenediamine, triethylenetetramine, and ethylenediamine; the resin particles are at least one of polyvinylidene fluoride particles, polyacrylic resin particles, and polyurethane particles.

3. The high-transmittance heat-insulating nano coating according to claim 1, characterized in that: The organic solvent is at least one of ethanol, isopropanol, ethyl acetate, butyl acetate, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, ethylene glycol diethyl ether, diethylene glycol butyl ether, and N-methylpyrrolidone; The resin is at least one of fluorocarbon resin, polyurethane resin, acrylic resin and silicone resin; The wetting and leveling agent is at least one of BYK346, BYK333, BYK-3550, TEGO Glide410, SURFYNOL420, DC-57, and Efka FL 3772.

4. The high-transmittance heat-insulating nano coating according to claim 1, characterized in that: The dispersant is at least one of BYK2015, BYK2018, BYK190, BYK110, BYK348, and TEGO-760W; The UV additives are TINUVIN 400, TINUVIN 477, TINUVIN 479, TINUVIN At least one of TINUVIN 1130, TINUVIN 292, TINUVIN 1130, TINUVIN 123, and TINUVIN 249; The film-forming aid is at least one of D-110, HT-100, N3390, D-120N, and D-3725.

5. A method for preparing a high-transmittance heat-insulating nano coating according to claims 1-4, characterized in that: The following steps are involved: S1. Add 0.01-0.5 parts of white oil, 0.1-1 parts of coupling agent, 0.01-1 parts of chain extender and 30-60 parts of resin particles into a high-speed mixer and mix them at 1500 rpm to obtain A; S2, 30nm cesium tungsten bronze powder, 50nm ATO powder, and 20nm lanthanum hexaboride powder are mixed in a ratio of 7:2:1 to obtain thermal insulation nanopowder, and then 10-30 parts of the thermal insulation nanopowder are added to A, and mixed to obtain B; S3, blending and extruding B through a planetary twin-screw extruder, and pelletizing after cooling to obtain a composite modified thermal insulation nanomaterial C; S4. Add 10-30 parts of C to 50-70 parts of organic solvent, stir until dissolved, and add 10-20 parts of resin, 0.1-1 parts of wetting and leveling agent, 0.1-1 parts of dispersant, 0.5-3 parts of UV additives, 0-5 parts of film-forming additives, stir evenly with a high-speed stirrer to obtain a high-transmittance heat-insulating nano coating.